Using reference equations to standardise incremental shuttle walk test performance in children and young people with chronic conditions and facilitate the evaluation of exercise capacity and disease severity - Eleanor Main; Melanie Bladen; Emma Raywood; Deepti Chugh; Nicole Filipow; Helen Douglas; Nicky Murray; Rachel O'Connor; Elisabeth Robinson; Nikki Thorpe (BMJ Open)
Aims The aim was to evaluate whether standardised exercise performance during the incremental shuttle walk test (ISWT) can be used to assess disease severity in children and young people (CYP) with chronic conditions, through (1) identifying the most appropriate paediatric normative reference equation for the ISWT, (2) assessing how well CYP with haemophilia and cystic fibrosis (CF) perform against the values predicted by the best fit reference equation and (3) evaluating the association between standardised ISWT performance and disease severity.Methods A cross-sectional analysis was carried out using existing data from two independent studies (2018–2019) at paediatric hospitals in London,UK. CYP with haemophilia (n=35) and CF (n=134) aged 5–18 years were included. Published reference equations for standardising ISWT were evaluated through a comparison of populations, and Bland-Altman analysis was used to assess the level of agreement between distances predicted by each equation. Associations between ISWT and disease severity were assessed with linear regression.Results Three relevant reference equations were identified for the ISWT that standardised performance based on age, sex and body mass index (Vardhan, Lanza, Pinho). A systematic proportional bias of standardised ISWT was observed in all equations, most pronounced with Vardhan and Lanza; the male Pinho equation was identified as most appropriate. On average, CYP with CF and haemophilia performed worse than predicted by the Pihno equation, although the range was wide. Standardised ISWT, and not ISWT distance alone, was significantly associated with forced expiratory volume in 1 s in CYP with CF. Standardised ISWT in CYP with haemophilia was slightly associated with haemophilia joint health score, but this was not significant.Conclusions ISWT performance may be useful in a clinic to identify those with worsening disease, but only when performance is standardised against a healthy reference population. The development of validated global reference equations is necessary for more robust assessment.